Analisis Tentang Perlindungan Hukum Pernikahan Dini Pada Usia di bawah 19 Tahun Menurut Hukum Islam - Ahmad Muhammad Mustain Nasoha; Hidayat, Ramdhan; Ashfiya Nur Atqiya (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
In maintaining the welfare of women and children involved in early marriage, legal protection has a very important role. This research uses doctrinal legal research which is a process to find rules, principles, and doctrines to answer the issues at hand. The characteristics of the research are prescriptive. The research method used is Normative / Doctrinal / Library Research Researchers concluded that to protect the Law of Early Marriage the age under 19 years according to Islamic law needs appropriate legal regulations, the need for women's empowerment and community education, inter-stakeholder cooperation in the context of the legal protection of early marriage from various parties, including government, non-governmental institutions, international organizations, and civil society. This collaboration is needed to formulate effective policies, provide adequate services, and raise public awareness. According to Islamic Fiqh itself, Marriage scholars differ on the minimum age of marriage. Most of the scholars of the Maliki madzhab argue that the age of menstruation for women and men is 17 years or 18 years, while Abu Hanifah argues that the age of puberty is 19 years or older. Shafi'i, Ahmad, Ibn Wahab, and the majority think that it is the perfect age of fifteen years.